(3ELGRI aj bQGAI CHj YeQh Hf GdYdG ef QhGjJj GdOhQj hGdShSj Yf WQjb GdTGWHjI hGdJjSjQs - (3eLghds ((3eMeO GdNGdOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hGLH GdhLhO dPGJg , GdefRg Yf GdJZjjQ aj PGJg hCSeGFg hUaGJg GdPj ef YdjfG HbQGAI GdbQBf hHYO abO bQC Ydj GdTjN GdEeGe GdTjN eMehO Hf GdTjN GdRGgO GdUGdM GdTgjQ HGdUeGOj bQGAI CHj YeQh Hf GdYdGA hbO CPfJ dg Cf jbQC HgG s
(3BNQgG (B:s
(3hefge (B( (3Cj ef bQC Ydjge GdeLjR (B) (3GdTjN Jbj GdOjf GdVQjQ GdYLdhfj hefge GdTjN GdTjN GdVQjQ ebQj GdReGf GdTjN CMeO Hf hQjS hcd gDdGA GdeTghQjf HGdUdGM hGdOjf hGdNjQ QMege Gddg JYGdi hQVj Yfge eJUdI GdCSGfjO Edi oCnHqj Hf cYH Edi GdfHj Udi Gddg Ydjg hSdes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdbQGAGJ hGdJLhjOs